Comparative Analysis of Staining Time Using Giemsa 10% on the Results of Malaria Blood Preparations - M. Richo Realdy Wirawan; Dwi Haryatmi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Malaria is a parasitic infectious disease that remains a significant public health problem in Indonesia, particularly in endemic areas. Rapid and accurate diagnosis of malaria is essential to prevent serious complications. The 10% Giemsa staining method is a rapid technique for microscopic examination of malaria, but the staining time standard needs to be validated for each batch of staining solution used in local laboratories. This study aims to analyze the comparison of malaria blood smear staining results using 10% Giemsa with different staining durations of 10 minutes, 20 minutes, and 30 minutes at Natar Medika Hospital. This research employed a cross-sectional approach with observational analysis of thin blood smears from 15 malaria-positive blood samples. The blood smear evaluation used a scoring system: a score of 0 was given for poor staining results (unclear background, unstained or non-blue cytoplasm, and unstained or non-red nucleus), and a score of 1 for good staining results (clear background, blue cytoplasm, and red nucleus). The results showed that staining for 20 minutes produced the best quality thin blood smears, characterized by a clear background, blue cytoplasm, and red nucleus. Statistical analysis using the Kruskal-Wallis test indicated significant differences between staining durations (p < 0.05). Therefore, staining for 20 minutes using 10% Giemsa is recommended to obtain optimal microscopic results in malaria diagnosis at Natar Medika Hospital.